The Public Place of the (Neo-)Victorians - Llewellyn, Mark (My University, 2017)
The Victorians are everywhere. Neo-Victorian adaptations of their writings, lives and culture are all around us in the contemporary marketplace. (Neo)Victorianism sells in its most popular forms, from blockbuster films, TV serialisations and bestselling novels. The public appetite for the nineteenth century and modern re-workings of it is therefore a given in a global cultural economy. How, though, do we academics engage those audiences, readers, viewers with the research on the Victorians and the neo-Victorian? What strategies might we consider to maximise the benefits, impacts and purpose of our scholarship to a society-at-large which is so attentive to creative interpretation but not necessarily critical approaches? This presentation will draw on my personal experience as a researcher in both Victorian and neo-Victorian studies. It will involve some highlights and low moments from my  own past projects engaging the public with the (neo)Victorian (be it in libraries, archives or public squares), and some suggestions for ways in which reciprocal engagement, co-production of research and the consideration of contemporary public concerns, can offer an entry point to scholarly debate. I will also draw on over five years of work as Director of Research at the UK’s Arts and Humanities Research Council, including examples from projects focussed on public engagement and partnership experience with museums, galleries, local history and community groups and organisations such as the BBC.
Keywords: Literatura inglesa; Neo-Victorian; Public engagement